Design of pile foundations using Eurocode 7 - Chen, Daryl Zhongwei. (2012)
Piles are usually classified into two main categories based on the method of installation. The common types are driven piles and bored piles. This project explores the design of bored piles in conjunction with newer introduction of the new Eurocode 7. In this report, the differences between the Eurocode 7 and the Conventional Method of pile design will be compared to examine the different trends that occur between the two. The comparisons are based on different scenarios to determine how pile design lengths and the overdesign factors are affected. The results show that the Conventional Method is less consistent in terms of pile design lengths and its overdesign factors. Although Eurocode 7 methods have more consistency for the overdesign factors, the pile design lengths are inconsistent for multiple layers analysis compared with a single profile characteristic. There were no clear conclusions as to which method is the most conservative in terms of design approach.